I don't know whether it is forbidden to post questions from other sites. However, this is from http://www.manhattangmat.com
. I apologize in advance if I violate any rule.
Here comes the question:
From 1 ) c + d = (r ^ 2)/(a + b)
= (a+b)^2 * (c-d)^2 / ( a+ b)
(a + b) can or cannot be a perfect square ,hence insufficient.
From 2) (a + b) is a perfect square. ( still no clue about c + d )
Using 1 and 2. c + d = (a+b) (c -d ) ^2
= (x^2*y^3*z)^2 * (c - d ) ^2
= ((x^2*y^3*z) * (c - d )) ^2.( a perfect square)